Long-term Outcomes for Living Pancreas Donors in the Modern Era. Issue 6 (June 2016) - Kirchner, Varvara A.; Finger, Erik B.; Bellin, Melena D.; Dunn, Ty B.; Gruessner, Rainer W.G.; Hering, Bernhard J.; Humar, Abhinav; Kukla, Aleksandra K.; Matas, Arthur J.; Pruett, Timothy L.; Sutherland, David E.R.; Kandaswamy, Raja
Abstract : Background: Living donor segmental pancreas transplants (LDSPTx) have been performed selectively to offer a preemptive transplant option for simultaneous pancreas-kidney recipients and to perform a single operation decreasing the cost of pancreas after kidney transplant. For solitary pancreas transplants, this option historically provided a better immunologic match. Although short-term donor outcomes have been documented, there are no long-term studies. Methods: We studied postdonation outcomes in 46 segmental pancreas living donors. Surgical complications, risk factors (RF) for development of diabetes mellitus (DM) and quality of life were studied. A risk stratification model (RSM) for DM was created using predonation and postdonation RFs. Recipient outcomes were analyzed. Results: Between January 1, 1994 and May 1, 2013, 46 LDSPTx were performed. Intraoperatively, 5 (11%) donors received transfusion. Overall, 9 (20%) donors underwent splenectomy. Postoperative complications included: 6 (13%) peripancreatic fluid collections and 2 (4%) pancreatitis episodes. Postdonation, DM requiring oral hypoglycemics was diagnosed in 7 (15%) donors and insulin-dependent DM in 5 (11%) donors. RSM with three predonation RFs (oral glucose tolerance test, basal insulin, fasting plasma glucose) and 1 postdonation RF, greater than 15% increase in body mass index from preoperative (Δ body mass index >15), predicted 12 (100%) donors that developed postdonation DM. Quality of life was not significantly affected by donation. Mean graft survival was 9.5 (±4.4) years from donors without and 9.6 (±5.4) years from donors with postdonation DM. Conclusions: LDSPTx can be performed with good recipient outcomes. The donation is associated with donor morbidity including impaired glucose control. Donor morbidity can be minimized by using RSM and predonation counseling on life style modifications postdonation. Abstract : Living donor segmental pancreas transplant can be performed with good recipient outcomes. The donation is associated with donor morbidity including impaired glucose control. Donor morbidity can be minimized by using a risk-stratification model and predonation counseling on lifestyle modifications postdonation.